Overview of the Integral Impact of MDVRP Routing Variables on Routing Heuristics - Morsidi, Farid; Panessai, Ismail Yusuf (Applied Information Technology And Computer Science, 2023)
The multi-depot VRP (MDVRP) is a variant of single-purpose VRP that is the potential in identifying the most effective routes for a group of vehicles while taking into account the capacity, cost, and time constraints for each vehicle. This is done by utilizing cutting-edge algorithms and optimization techniques. To reduce the cost and time incurred by all vehicles, MDVRP can also optimize the route for each one of them. This paper presents a review of the research methodologies used over the years to examine the benefits and characteristics of MDVRP instances in resolving real-world issues. The paper also discusses the various algorithms and optimization methods used to resolve MDVRP instances and how they can be utilized to save time and money while maintaining a high level of service. The paper also discusses the MDVRP’s potential uses in logistics and transportation, including resource allocation, scheduling, and route planning.